A mesoporous silica molecular sieve doped hydrogel composite scaffold and its preparation method and application
Hydrogel composite brackets with long-term sustained release oxygen and high mechanical strength were prepared by loading calcium peroxide in hydrogels with mesoporous silica molecular sieves and combined with acrylamide/sodium alginate-based hybrid dual network hydrogels. , solve the shortcomings of existing oxygen-producing hydrogels in terms of oxygen release time and mechanical strength, and achieve effective support for bone defect repair.
Patent Information
- Application Number
- CN202411440826.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing oxygen-producing hydrogels have shortcomings in oxygen release time and mechanical strength, and cannot effectively support bone defect repair.
Mesoporous silicon oxide molecular sieve was used to load calcium peroxide and added to acrylamide/sodium alginate-based hybrid dual network hydrogel. The hydrogel composite scaffold was prepared by 3D printing technology.
The long-term sustained release of oxygen is achieved, the oxygen release time is extended, and the mechanical strength of the hydrogel composite scaffold is improved, which can effectively support bone regeneration.
Smart Images

Figure CN118949139B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of colloid chemistry, and relates to a self-oxygenating hydrogel, in particular to a mesoporous silica molecular sieve doped hydrogel composite scaffold, and a preparation method and application thereof. Background Art
[0002] Reconstruction of large bone defects caused by severe trauma, tumor resection, and congenital malformations has always been a serious problem faced by patients and orthopedic surgeons around the world. Traditional bone repair treatment methods mainly use autologous transplantation, allograft transplantation, or synthetic bone substitute materials to fill bone defects and provide structural support, but their further application is limited by the scarcity of bone donors, bone size mismatch, immune rejection, and poor integration with surrounding bone tissue. Therefore, advanced bone substitute materials are urgently needed to effectively solve these problems.
[0003] Bone tissue engineering is a new treatment method to promote bone healing, which aims to repair bone defects through a combination of various polymer scaffolds, cells and growth factors. Bone is a highly vascularized tissue that relies on blood vessels to provide necessary nutrients and oxygen. Many studies have shown that the delivery of cells or growth factors can effectively stimulate angiogenesis and osteogenesis, but factors such as short half-life, high cost and limited resources limit their widespread application. Therefore, a scaffold without cells or growth factors is needed to promote vascularized bone regeneration for further clinical treatment. Hydrogels have attracted much attention in the field of bone tissue engineering due to their outstanding features such as similar structure to extracellular matrix, porous internal structure and good toughness, and can be highly precise and personalized through 3D printing.
[0004] Studies have shown that timely and sufficient oxygen supply before angiogenesis can prevent tissue necrosis and improve cell survival rate, and can also promote tissue repair by enhancing the expression of vascular-related genes and the differentiation of osteoblasts. Materials that release oxygen can generally be divided into oxygen-carrying materials and oxygen-producing materials. Among them, the oxygen-producing material calcium peroxide is considered to be a promising material that can decompose in water to produce oxygen. But the basic problem with the use of calcium peroxide is that it may cause rapid release of oxygen, which may further damage the surrounding tissue. People can extend the oxygen production time to one week by introducing calcium peroxide into hydrogels. Sanika Suvarnapathaki et al. (Bioactive Materials, 2022, 13: 64–81) extended the oxygen generation time to two weeks by encapsulating calcium peroxide in polycaprolactone microspheres, but the compression modulus of the resulting scaffold was only about 20KPa, which may not be enough to support bone defect repair. Summary of the invention
[0005] In order to overcome the shortcomings of the current oxygen-generating hydrogel, such as short oxygen-generating time and insufficient mechanical strength, the present invention provides a mesoporous silica molecular sieve-doped hydrogel composite scaffold and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is: a method for preparing a mesoporous silica molecular sieve doped hydrogel composite scaffold, using mesoporous silica molecular sieve loaded with calcium peroxide to obtain M-SiO2-CaO2, adding it to an acrylamide / sodium alginate based mixed double network hydrogel, and obtaining a hydrogel composite scaffold after curing.
[0007] Preferably, the specific steps are as follows:
[0008] Step 1: CaCl2 is loaded into the pores of the mesoporous silica molecular sieve by impregnation, and dried to obtain a white powder. A mixed solution of NH3·H2O and H2O2 is then impregnated into the white powder, and after standing for reaction, the powder is fully washed until there are no more chloride ions in the solution, and dried to obtain M-SiO2-CaO2;
[0009] Step 2: dissolving acrylamide in deionized water, adding L-glutamic acid, M-SiO2-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and photoinitiator in sequence, and stirring to obtain hydrogel bio-ink;
[0010] Step 3: After the hydrogel bio-ink is solidified, a hydrogel composite scaffold is obtained.
[0011] Preferably, in step 1, the molar ratio of mesoporous silica molecular sieve, CaCl2, NH3·H2O, and H2O2 is 100: 10-30: 3-5: 3-5; the mesoporous silica molecular sieve is one or more of MCM-41, HMS, and SBA-15.
[0012] Preferably, step 2 is specifically to dissolve acrylamide in deionized water under stirring at 50-60 ° C, then add L-glutamic acid and continue stirring for at least 0.5 h, then turn off the heating and cool to room temperature; then add M-SiO2-CaO2 and ultrasonically disperse it, then add sodium alginate and stir for at least 0.5 h, then add calcium silicate, N,N-methylenebisacrylamide and photoinitiator in sequence, and stir for at least 0.5 h to obtain hydrogel bio-ink; wherein the mass ratio of deionized water, acrylamide, L-glutamic acid, M-SiO2-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and photoinitiator is 100: 20-25: 1-2: 2-5: 10-12: 1-2: 0.5-1: 0.9-2.
[0013] Preferably, the photoinitiator is one or more of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, uranyl ion and ammonium persulfate.
[0014] Preferably, the specific preparation method in step three is to print the hydrogel bio-ink into a specific preset shape based on 3D printing technology, and use ultraviolet light to solidify it during the printing process.
[0015] Preferably, the hydrogel composite scaffold obtained by printing and curing is immersed in a calcium chloride aqueous solution for further curing, and the mass concentration of the calcium chloride aqueous solution is 10-30%.
[0016] The hydrogel bio-ink or hydrogel composite scaffold prepared by the preparation method of mesoporous silica molecular sieve doped hydrogel composite scaffold.
[0017] The invention discloses a method for preparing a mesoporous silica molecular sieve doped hydrogel composite scaffold and uses the prepared hydrogel composite scaffold in bone injury repair.
[0018] The advantages and positive effects of the present invention are as follows: oxygen-generating particles of calcium peroxide are loaded on a one-dimensional mesoporous silicon oxide molecular sieve; the mesoporous structure is less likely to be blocked than the microporous structure; and the one-dimensional mesoporous channel structure can slowly release oxygen, so that the prepared material has a large amount of long-term slow release of oxygen; in the preparation process, the ratio of calcium chloride and molecular sieve is adjusted so that the calcium peroxide grows inside the channels of the mesoporous silicon dioxide molecular sieve, and does not grow outside the channels to cause sudden release of oxygen;
[0019] During the synthesis of the hydrogel composite scaffold, sodium alginate and calcium ions are cross-linked to form the first network, and then polyacrylamide is cross-linked under ultraviolet light to form the second network. Supported by the mixed double network, the hydrogel composite scaffold has excellent strength and toughness, which improves the mechanical strength of the composite scaffold; after 3D printing, the sample is immersed in a calcium chloride aqueous solution to allow it to further cross-link with calcium ions, further improving its compressive strength;
[0020] Based on the above advantages, the hydrogel composite material can be used as bone damage repair material. The characteristic of large-scale long-term oxygen release effectively prolongs the oxygen release time to promote the reconstruction of the vascular network and support bone regeneration for a long time. The excellent strength and toughness are also sufficient to support bone regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Photo of the 3D printed hydrogel composite scaffold GEL-1 obtained in Example 1;
[0022] Figure 2 Evaluation diagram of 3D printed hydrogel composite scaffold GEL-1 and blank group for the repair of skull defects in SD rats. DETAILED DESCRIPTION
[0023] The embodiments of the present invention are described below with reference to the accompanying drawings.
[0024] The present invention relates to a mesoporous silica molecular sieve doped hydrogel composite scaffold and its preparation method and application. M-SiO2-CaO2 is obtained by loading oxygen-producing particles of calcium peroxide using one-dimensional mesoporous silica molecular sieves such as MCM-41, HMS and SBA-15, and then added into acrylamide / sodium alginate-based mixed double network hydrogel to form hydrogel bio-ink, which is prepared into a specific shape structure by 3D printing technology, and then solidified to form a hydrogel composite scaffold. The hydrogel composite scaffold increases the calcium peroxide loading amount, realizes a sustained release effect based on the pore structure of the mesoporous molecular sieve, effectively prolongs the oxygen production time, and the hydrogel composite scaffold has excellent mechanical strength.
[0025] The specific preparation process of the mesoporous silica molecular sieve doped hydrogel composite scaffold is as follows:
[0026] Step 1: Synthesis of mesoporous silica molecular sieve-CaO2 (M-SiO2-CaO2) slow-release oxygen-generating particles; CaCl2 is loaded into the pores of the mesoporous silica molecular sieve by impregnation, and then the sample is thoroughly dried to obtain a white powder, and then a mixed solution of NH3·H2O and H2O2 is impregnated into the white powder, and after standing for at least 1 hour, the sample is washed with deionized water until there are no more chloride ions in the solution, and then the solid powder is dried to obtain M-SiO2-CaO2, and the drying temperature is not higher than 100°C;
[0027] Among them, the mesoporous silica molecular sieve is one or more of MCM-41, HMS, and SBA-15; MCM-41, HMS, and SBA-15 one-dimensional mesoporous silica molecular sieves are used to load oxygen-producing particles of calcium peroxide. Compared with the microporous structure, the mesoporous structure is not easy to be blocked, and its one-dimensional mesoporous channel structure can slowly release oxygen, effectively prolong the oxygen release time to promote the reconstruction of the vascular network, and support bone regeneration for a long time. The molar ratio of mesoporous silica molecular sieve, CaCl2, NH3·H2O, and H2O2 is 100: 10-30: 3-5: 3-5. Excessive calcium chloride can completely convert hydrogen peroxide, otherwise the residual hydrogen peroxide may be toxic to cells, wherein the unreacted calcium chloride can remove chloride ions by washing. In addition, this molar ratio can make calcium peroxide grow inside the pores of the mesoporous silica molecular sieve, and will not grow outside the pores to cause sudden release of oxygen.
[0028] Step 2: Synthesis of hydrogel bio-ink; dissolve acrylamide in deionized water under stirring at 50-60 °C, then add L-glutamic acid and continue stirring for at least 0.5 h, then turn off the heating and cool to room temperature; then add the M-SiO2-CaO2 prepared in step 1 and ultrasonically disperse it, then add sodium alginate and stir for at least 0.5 h, then add calcium silicate, N,N-methylenebisacrylamide and photoinitiator to the above mixture in sequence, and stir for at least 0.5 h to obtain hydrogel bio-ink.
[0029] Acrylamide monomers polymerize to form polyacrylamide under the action of photoinitiators, and the formed linear polymer chains are interconnected under the action of cross-linker N,N-methylenebisacrylamide to form polyacrylamide hydrogels with chemical (covalent) networks. Sodium alginate will undergo ion exchange with calcium ions in calcium silicate to form calcium alginate hydrogels with physical networks. Traditionally, calcium chloride is used as a cross-linking agent, but calcium chloride will quickly release calcium ions to cross-link with sodium alginate, and the formed calcium alginate beads cannot be 3D printed. Therefore, insoluble calcium salt calcium silicate is used, and L-glutamic acid that can provide an acidic environment is introduced to stimulate calcium silicate to slowly release calcium ions and cross-link with sodium alginate.
[0030] The photoinitiator is one or more of 2,2-azobis(2-methylpropylimidamide) dihydrochloride, uranyl ion and ammonium persulfate; the mass ratio of deionized water, acrylamide, L-glutamic acid, M-SiO2-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and photoinitiator is 100: 20-25: 1-2: 2-5: 10-12: 1-2: 0.5-1: 0.9-2.
[0031] Step 3: Load the hydrogel bio-ink into the sample tube of the 3D printer and print it according to the designed 3D model. During the printing process, the printed hydrogel bio-ink is irradiated with ultraviolet light to further photocuring the hydrogel bio-ink. During the synthesis of the hydrogel composite scaffold, the calcium ions in sodium alginate and calcium silicate are cross-linked to form the first network, and then the polyacrylamide is cross-linked under the irradiation of ultraviolet light to form the second network. Supported by the mixed double network, the hydrogel composite scaffold has excellent strength and toughness, which is sufficient to support bone regeneration.
[0032] After printing is completed, the sample is immersed in a calcium chloride aqueous solution for at least 0.5 hours, and the mass concentration of the calcium chloride aqueous solution is 10-30%; the purpose is to allow it to further cross-link with calcium ions and improve its compressive strength; then the sample is taken out and sealed for storage to obtain a hydrogel composite scaffold.
[0033] The hydrogel composite scaffold prepared by the above method has the function of self-oxygenation, which can achieve slow release of oxygen, prolong oxygen release time, and ensure excellent mechanical strength; based on such characteristics, it can be used instead of bone powder in bone damage repair materials. The long-term oxygen supply promotes the reconstruction of the vascular network and effectively promotes vascularized bone regeneration for a long time; the excellent strength and toughness, as well as high compressive strength, enable it to achieve the support function of regenerated bones.
[0034] The scheme of the present invention is described below with reference to the accompanying drawings and tables, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.
[0035] Example 1
[0036] (1) CaCl2 was loaded into the pores of MCM-41 by impregnation, and then the sample was thoroughly dried to obtain a white powder. Subsequently, a mixed solution of NH3·H2O and H2O2 was impregnated into the white powder. After standing for 1 h, the sample was washed with deionized water until there were no more chloride ions in the solution. The solid powder was then dried to obtain MCM-41-CaO2. The molar ratio of MCM-41, CaCl2, NH3·H2O, and H2O2 was 100:10:3:3.
[0037] (2) Under stirring at 50 °C, acrylamide was dissolved in deionized water, and then L-glutamic acid was added and stirred for 0.5 h, and then the heating was turned off and cooled to room temperature; MCM-41-CaO2 was then added and ultrasonically dispersed, and then sodium alginate was added and stirred for 0.5 h. Calcium silicate, N,N-methylenebisacrylamide and 2,2-azobis(2-methylpropylimidamide) dihydrochloride were added to the above mixture in sequence and stirred for 0.5 h to obtain hydrogel bio-ink; wherein the mass ratio of deionized water, acrylamide, L-glutamic acid, MCM-41-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and photoinitiator was 100:20:1:2:10:1:0.5:0.9.
[0038] (3) The hydrogel bio-ink is loaded into the sample tube of the 3D printer and printed according to the designed 3D model. During the printing process, the printed hydrogel bio-ink is irradiated with ultraviolet light to further photocuring the hydrogel bio-ink. After the printing is completed, the sample is immersed in a 30% by mass calcium chloride aqueous solution for 0.5 h, and then the sample is taken out and sealed for storage. The obtained hydrogel composite scaffold is numbered GEL-1. The product structure is shown in FIG. Figure 1 As shown, it can be seen that the prepared hydrogel bio-ink can obtain a structurally stable composite structure through 3D printing.
[0039] Example 2
[0040] The preparation steps of Example 2 are the same as those of Example 1, except that the MCM-41 carrier in step (1) is replaced by an HMS carrier, the standing time after immersion in a mixed solution of NH3·H2O and H2O2 is changed to 2 h, and the molar ratio of HMS, CaCl2, NH3·H2O, and H2O2 is changed to 100:20:4:4. The resulting hydrogel composite scaffold is numbered GEL-2.
[0041] Example 3
[0042] The preparation steps of Example 3 are the same as those of Example 1, except that the MCM-41 carrier in step (1) is replaced by an SBA-15 carrier, and the molar ratio of SBA-15, CaCl2, NH3·H2O, and H2O2 is changed to 100:30:5:5. The resulting hydrogel composite scaffold is numbered GEL-3.
[0043] Example 4
[0044] The preparation steps of Example 4 are the same as those of Example 1, except that 2,2-azobis(2-methylpropylimidamide) dihydrochloride in step (2) is replaced by uranyl ions, and the mass ratio of deionized water, acrylamide, L-glutamic acid, MCM-41-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and uranyl ions is changed to 100:22.5:1.5:3.5:11:1.5:0.75:1.45. The resulting hydrogel composite scaffold is numbered GEL-4.
[0045] Example 5
[0046] The preparation steps of Example 5 are the same as those of Example 1, except that 2,2-azobis(2-methylpropylimidamide) dihydrochloride in step (2) is replaced by ammonium persulfate, and the mass ratio of deionized water, acrylamide, L-glutamic acid, MCM-41-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and ammonium persulfate is changed to 100:25:2:5:12:2:1:2. The resulting hydrogel composite scaffold is numbered GEL-5.
[0047] Example 6
[0048] The preparation steps of Example 6 are the same as those of Example 1, except that the mass concentration of the calcium chloride solution in step (3) is changed to 10%, and the immersion time is changed to 1 h. The obtained hydrogel composite scaffold is numbered GEL-6.
[0049] Example 7
[0050] The preparation steps of Example 7 are the same as those of Example 1, except that the mass concentration of the calcium chloride solution in step (3) is changed to 20%, and the immersion time is changed to 2 h. The obtained hydrogel composite scaffold is numbered GEL-7.
[0051] Comparative Example 1
[0052] The purpose is to compare with Example 1 to illustrate the effect of the carrier used to load calcium peroxide on the oxygen production time of the composite stent.
[0053] The preparation steps of Comparative Example 1 are the same as those of Example 1, except that the MCM-41 used in step (1) is replaced by MCM-48, and the obtained hydrogel composite scaffold is numbered GEL-8.
[0054] Comparative Example 2
[0055] The purpose is to compare with Example 1 to illustrate the effect of a larger molar ratio of MCM-41, CaCl2, NH3·H2O, and H2O2 on the oxygen production time of the composite stent.
[0056] The preparation steps of Comparative Example 2 are the same as those of Example 1, except that the molar ratio of MCM-41, CaCl2, NH3·H2O, and H2O2 in step (1) is 100:5:1:1, and the resulting hydrogel composite scaffold is numbered GEL-9.
[0057] Comparative Example 3
[0058] The purpose is to compare with Example 1 to illustrate the effect of a relatively small molar ratio of MCM-41, CaCl2, NH3·H2O, and H2O2 on the oxygen production time of the composite stent.
[0059] The preparation steps of Comparative Example 3 are the same as those of Example 1, except that the molar ratio of MCM-41, CaCl2, NH3·H2O, and H2O2 in step (1) is 100:40:7:7, and the resulting hydrogel composite scaffold is numbered GEL-10.
[0060] Comparative Example 4
[0061] The purpose is to compare with Example 1 to illustrate the effect of the concentration of the calcium chloride solution used to soak the stent after printing on the mechanical properties of the composite oxygen-generating stent.
[0062] The preparation steps of Comparative Example 4 were the same as those of Example 1, except that the mass concentration of the calcium chloride solution used in step (3) was changed to 1%. The obtained hydrogel composite scaffold was numbered GEL-11.
[0063] Example 8: Detection of hydrogel composite scaffold
[0064] 8.1 Characterization of the oxygen-generating cycle of oxygen-generating hydrogels
[0065] The hydrogel bio-ink obtained in step (2) of Example 1-7 and Comparative Example 1-3 was squeezed into a customized cylindrical polytetrafluoroethylene mold and cured by ultraviolet light to obtain a hydrogel cylinder. First, a certain amount of PBS was placed in a reagent bottle, and the PBS was deoxygenated by bubbling with nitrogen for 10 minutes. Then, the obtained hydrogel cylinder was immersed in PBS, and the reagent bottle was sealed and placed in a 37 ° C oven. The dissolved oxygen in PBS was measured every two days using a dissolved oxygen meter (DO-958-BF, China Inest Company), and nitrogen was used for deoxygenation after each measurement. The test results are shown in Table 1. By comparison, it can be seen that the hydrogels prepared in Examples 1-7 can slowly release oxygen and have a longer oxygen production cycle.
[0066] Table 1
[0067]
[0068] For vascularized bone regeneration, the ideal oxygen release is slow oxygen release and a long oxygen release cycle. Explosive oxygen release will damage normal cells and tissues. The oxygen release cycle of the hydrogel composite scaffold prepared in the embodiment and the comparative example is 18 days, and basically no oxygen is released after 18 days. As can be seen from the data in Table 1, GEL-1-GEL-7 can all achieve slow oxygen release, and after GEL-8 replaces the silica carrier with a one-dimensional pore with the carrier MCM-48 with a three-dimensional pore, the scaffold will release oxygen explosively in the first few days, and too much oxygen will cause toxic effects on cells, and the oxygen production cycle is only 10 days; GEL-9 reduces the amount of calcium chloride, ammonia water, and hydrogen peroxide, and the scaffold produces less oxygen and has a shorter release cycle; GEL-10 increases the amount of calcium chloride, ammonia water, and hydrogen peroxide, and the scaffold also releases oxygen explosively in the first few days, and the oxygen release cycle is short. This is because after the increase in dosage, part of the calcium peroxide grows outside the silica carrier pore. It can be seen that the GEL-1 prepared with a suitable silica carrier and a suitable raw material ratio can slowly release oxygen and achieve a longer oxygen release period.
[0069] 8.2 Characterization of Mechanical Properties of Oxygen-generating Hydrogels
[0070] The hydrogel bio-ink obtained in step (2) of Examples 1-7 and Comparative Example 4 was squeezed into a customized cylindrical polytetrafluoroethylene mold and irradiated with a UV lamp to cure it to obtain a hydrogel cylinder. The mechanical properties of the hydrogel cylinder were measured by a universal testing machine (Instron 5567, Instron, USA). The specific implementation method was as follows: the hydrogel cylinder was installed between two parallel pressing plates and the pressure was adjusted at 5 mm / min. -1The hydrogel cylinder was compressed at a constant strain rate until it was completely damaged, and its compressive strength was obtained. The results are shown in Table 2. It can be seen that the mechanical properties of GEL-1 prepared in Examples 1-7 are significantly higher than those of GEL-11 prepared in Comparative Example 4. When the concentration of calcium chloride used for soaking was reduced to 1% during the preparation of GEL-11, the mechanical strength was greatly reduced because the sodium alginate was not more fully cross-linked.
[0071] Table 2
[0072]
[0073] 8.3 Evaluation of the effect of oxygen-generating hydrogel scaffolds on bone defect repair
[0074] The bone defect repair effect of the oxygen-producing hydrogel composite scaffold in Example 1 was evaluated based on the SD rat skull defect model. In short, two circular bone defects with a diameter of 5 mm were first created on both sides of the rat skull suture, and then the wound was left untreated or oxygen-producing hydrogel scaffolds were placed for experiments. Skull samples from the blank group and the oxygen-producing scaffold group were collected at 4 weeks and 12 weeks for micro-CT scanning and reconstruction. The results are shown in the figure. Figure 2 As shown, the hydrogel composite scaffold prepared in Example 1 can significantly improve the repair rate in bone defect repair.
[0075] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a mesoporous silica molecular sieve doped hydrogel composite scaffold, characterized in that: Mesoporous silica molecular sieves were loaded with calcium peroxide to obtain M-SiO2-CaO2, which was added to acrylamide / sodium alginate-based mixed double network hydrogel and cured to obtain a hydrogel composite scaffold. The specific steps are as follows: Step 1: CaCl2 is loaded into the pores of the mesoporous silica molecular sieve by impregnation, and dried to obtain a white powder, and then a mixed solution of NH3·H2O and H2O2 is impregnated into the white powder, and after standing for reaction, the mixed solution is fully washed until there are no more chloride ions in the solution, and dried to obtain M-SiO2-CaO2; the molar ratio of the mesoporous silica molecular sieve, CaCl2, NH3·H2O, and H2O2 is 100:10-30:3-5:3-5; Step 2: Under stirring at 50-60 ° C, acrylamide is dissolved in deionized water, and then L-glutamic acid is added and continued to be stirred for at least 0.5 h, and then the heating is turned off and cooled to room temperature; then M-SiO2-CaO2 is added and ultrasonically dispersed, and then sodium alginate is added and stirred for at least 0.5 h, and then calcium silicate, N,N-methylenebisacrylamide and photoinitiator are added to the above mixture in sequence, and stirred for at least 0.5 h to obtain hydrogel bio-ink; wherein the mass ratio of deionized water, acrylamide, L-glutamic acid, M-SiO2-CaO2, sodium alginate, calcium silicate, N,N-methylenebisacrylamide and photoinitiator is 100: 20-25: 1-2: 2-5: 10-12: 1-2: 0.5-1: 0.9-2; Step 3: Print the hydrogel bio-ink into a specific preset shape based on 3D printing technology, and use ultraviolet light to solidify it during the printing process.
2. The method for preparing the mesoporous silica molecular sieve doped hydrogel composite scaffold according to claim 1, characterized in that: The mesoporous silica molecular sieve is one or more of MCM-41, HMS and SBA-15.
3. The method for preparing the mesoporous silica molecular sieve doped hydrogel composite scaffold according to claim 1, characterized in that: The photoinitiator is one or more of 2,2-azobis(2-methylpropylimidazole) dihydrochloride, uranyl ion and ammonium persulfate.
4. The method for preparing the mesoporous silica molecular sieve doped hydrogel composite scaffold according to claim 1, characterized in that: The hydrogel composite scaffold obtained by printing and curing is immersed in a calcium chloride aqueous solution for further curing, and the mass concentration of the calcium chloride aqueous solution is 10-30%.
5. The hydrogel bio-ink or hydrogel composite scaffold prepared by the method for preparing the mesoporous silica molecular sieve doped hydrogel composite scaffold according to any one of claims 1 to 4.
6. Use of the hydrogel composite scaffold prepared by the method for preparing the mesoporous silica molecular sieve doped hydrogel composite scaffold as claimed in any one of claims 1 to 4 in bone damage repair materials.
Citation Information
Patent Citations
Derailer
CA100407A
Method for preparing high-strength double-network nano silicon dioxide composite hydrogel
CN104262881A
Mesoporous silica based reactive oxygen species (ROS) radiation sensitizer and preparation method thereof
CN107281220A